The collected works (gsuṅ-ʼbum) of Rgod-tshaṅ-pa Mgon-po-rdo-rje - Rgod-tshaṅ-pa Mgon-po-rdo-rje, 1189-1258 (Kargyud Sungrab Nyamso Khang, 1972)
Writings on religious practice by the founder of the "Upper" branch of the Drukpa Kargyudpa sect of Tibetan Lamaism.